2010
DOI: 10.4314/sajas.v39i1.61174
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary lipid sources on production performance of broilers

Abstract: ________________________________________________________________________________ AbstractA study was conducted to determine the influence of different dietary lipid sources and inclusion levels on production performance of male broilers. Eight isoenergetic (15.1 MJ AME/kg DM) and isonitrogenous (223 g CP/kg DM) diets were formulated, using high oleic sunflower oil (HO), sunflower oil (SO), fish oil (FO) and tallow (T) at a 30 g/kg and 60 g/kg dietary inclusion level. Eight hundred (800), dayold Ross 788 broile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Numerous studies have reported that poultry, which received diets containing oil showed a better growth and laying performance (Joshi and Sell 1964;Bragg et al 1973;de Witt et al 2009). Moreover, in laying hens farming in China, 3-4% canola oil or soybean oil (SO) is commonly included in the daily feed.…”
Section: Introductionmentioning
confidence: 98%
“…Numerous studies have reported that poultry, which received diets containing oil showed a better growth and laying performance (Joshi and Sell 1964;Bragg et al 1973;de Witt et al 2009). Moreover, in laying hens farming in China, 3-4% canola oil or soybean oil (SO) is commonly included in the daily feed.…”
Section: Introductionmentioning
confidence: 98%
“…Similar effect was reported by Jamorz et al (2005) who indicated no improvement in body weight by dietary plant extract of broiler. De Witt et al (2009) and Fébel et al (2008) pointed out that diet supplementation with different sources of oils were not affect significant on the growth of birds. In contrast, Mohammed and Razaaq (2020) observed that increased live body weight due to higher moisture content in lettuce leaves leads to increased weight gain.…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion of soybean oil had improved body weight gain and reduced FCR compared with tallow in chicken indicated by Zhang et al (2011). In addition, Febel et al (2008 and De Witt et al (2009) reported that dietary inclusion with soy oil had no beneficial effect on the FI and FCR of chicken.…”
Section: Resultsmentioning
confidence: 99%